Интерното известување во хотелската индустрија во Република Македонија - Мирческа, Ирина (Економски факултет, УКИМ, Скопје, 2015)
Accounting and harmonized financial reporting is gaining in importance. This paper examines the internal reporting of the Hospitality industry in the Republic of Macedonia. The research performed focuses on the explicit theoretical analysis of the accounting system of the entire Hospitality industry. The responsibility principle emphasizes the need to develop responsible accounting, along with system segmentation. This is the base of the Unified System of Accounts in the Hospitality Industry, which will be examined in greater detail. There are multiple models of internal reporting developed for managing the accounting processes in the Hospitality industry so far. In the Republic of Macedonia, the traditional systems of managing the accounting processes are mainly used. This creates various difficulties when they are being modernized. Signifying the need to expand available options when attempting to implement a Unified System into the Macedonian hospitality companies. The above will be highlighted through practical exercises with concrete examples; where the possibility of the recommended system implementation is examined, while the foreseen difficulties to be overcome are enumerated. Through quantitative analysis, a realistic perspective of the accounting in the Hospitality industry in the Republic of Macedonia will be presented.
Докторска дисертација одбранета во 2015 година на Економскиот факултет во Скопје, под менторство на проф. д–р Блажо Недев.
Keywords: internal reporting, unified accounting system, responsibility of accounting, segments